Pengembangan Lembar Kerja Peserta Didik (LKPD) Matematika Untuk Siswa Tunarungu (SDLB-B) - Hedia Rizki; Kamid Kamid; Saharudin Saharudin (Edumatika : Jurnal Riset Pendidikan Matematika, 2018)
This research is aimed at describing the development of students’ worksheets of a mathematics subject for deaf students and finding out the effectivity of mathematics worksheets for deaf students toward the learning process. Multiplication is selected due to its ability to represent mathematics subjects which will be developed for deaf students. This research uses research and development method (R&D) with 6 deaf subjects in grade V in special needs education Sri Soedewi Masjchun Sofwan Jambi. This research applies the ADDIE model, analysis, design, development, implementation, and evaluation. The data collected are qualitative and quantitative. Qualitative data are collected from media expert validity and learning design, material expert validity, teachers’ respond from deaf class, and questionnaire result of students’ perception of learning media which has been created. Meanwhile, quantitative data are collected from the final test. Valid students’ worksheet is based on the questionnaire administered to the validator. 79% of students’ responds show positive respond and 83,3% of learning completion. It shows that mathematics worksheets developed feasible to use in the learning process.